Perceptions of School Subjects and Student Achievement as Factors of Orientation towards Mathematics and Natural Sciences in High School - Aleksandra S. Maksimović; Aleksandar Z. Milenković; Filip G. Stašević (University of Belgrade, Teacher Education Faculty, 2024)
Numerous studies point to the presence of a specific dichotomy in contemporary circumstances. On the one hand, it is emphasized that the knowledge of natural sciences is necessary for the progress of society. On the other hand, there are clear indicators of a decline in students' interest in mathematics, physics, biology, and chemistry. In this context, analysing the continuity of students' interest in teaching subjects is raised as relevant. Previous research on students' perceptions of different school subjects did not specifically take into account the students' majors and their attitudes towards the subjects. This study aims to investigate the high school students' perceptions of their educational experience in primary school, comparing the responses of the students enrolled in science-intensive programs to those of other students. We researched a sample of 1045 students from four high schools in Kragujevac and Novi Sad. Using an online questionnaire, we examined the following: the overall students' achievement in primary school in terms of final grades, their favourite subject in primary school, and their perceptions of the difficulty, usefulness, and interest of the subjects in primary school. The results show that students enrolling in natural sciences and specialized programs in mathematics, computer science, physics, biology, and chemistry have better overall academic performance than other students. Moreover, they significantly prefer mathematics, computer science, and physics. Additionally, these students perceive mathematics, computer science, physics, and chemistry, but not biology, as considerably less difficult and rate them as more interesting and useful compared to other students.